Study Of The Cinnamomum Clan As An Antidiabetic - Budi Yasri; Soraya Riyanti (Jurnal Indonesia Sosial Teknologi, 2023)
Ethnopharmacological research is an approach to exploring the local knowledge of specific communities about the use of medicinal plants. This article discusses the use of cinnamon (Cinnamomum) as an effective alternative medicine ingredient in several regions in Indonesia. The method used with data collection through literature search has been published in scientific research articles and journals. A literature search uses search engines published on several sites, such as Google Scholar, Pubmed, and Science Direct. Based on the review, it can be concluded that the Cinnamomum clan is widely used in various ethnic groups in Indonesia as a natural ingredient to help control blood glucose levels and is used as an alternative supplement for people with diabetes mellitus. Among the species of the genus Cinnamomum that have the potential to help control blood glucose levels are Cinnamomum burmanii, Cinnamomum verum, Cinnamomum tamala, and Cinnamomum zeylanicum.